2012
DOI: 10.1525/bio.2012.62.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Creating Wetlands: Primary Succession, Water Quality Changes, and Self-Design over 15 Years

Abstract: The succession of vegetation, soil development, water quality changes, and carbon and nitrogen dynamics are summarized in this article for a pair of 1-hectare flow-through-created riverine wetlands for their first 15 years. Wetland plant richness increased from 13 originally planted species to 116 species overall after 15 years, with most of the increase occurring in the first 5 years. The planted wetland had a higher plant community diversity index for 15 years, whereas the unplanted wetland was more producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(113 citation statements)
references
References 45 publications
1
109
0
3
Order By: Relevance
“…The wetlands were used extensively for wetland research from 1991 to 2012 and some of that research is reported here and in the accompanying special issue (see Mitsch et al, 2014a). The two kidney-shaped wetlands have been compared since water was first added on in 1994 (year 1), with research results regarding water quality, plant community structure and function, soil development, sedimentation, and gas exchange (see Mitsch et al, 1998Mitsch et al, , 2005aMitsch et al, ,b, 2012 for summaries at various years). These urban wetlands are located at the easternmost edge of the Central Plains portion of the Eastern Temperate Forest ecological region (biome) of North America and close to the intersection of three level II ecoregions in that biome: Mixed Wood Plains, Central Plains, and Appalachian Forests.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The wetlands were used extensively for wetland research from 1991 to 2012 and some of that research is reported here and in the accompanying special issue (see Mitsch et al, 2014a). The two kidney-shaped wetlands have been compared since water was first added on in 1994 (year 1), with research results regarding water quality, plant community structure and function, soil development, sedimentation, and gas exchange (see Mitsch et al, 1998Mitsch et al, , 2005aMitsch et al, ,b, 2012 for summaries at various years). These urban wetlands are located at the easternmost edge of the Central Plains portion of the Eastern Temperate Forest ecological region (biome) of North America and close to the intersection of three level II ecoregions in that biome: Mixed Wood Plains, Central Plains, and Appalachian Forests.…”
Section: Experimental Designmentioning
confidence: 99%
“…Our research team has been investigating the ecosystem services of inland wetlands for 20 years in a multi-year, whole-ecosystem experiment in two 1-ha created freshwater riverine flow-through marshes at Olentangy River Wetland Research Park at The Ohio State University, Columbus, Ohio, USA. Mitsch et al, 1998Mitsch et al, , 2005aMitsch et al, ,b, 2012 described ecological services and function of these wetlands at years 3, 5, 10, and 15, including the succession and ecosystem function of these wetland laboratories, This paper investigates the change in vegetation succession and nutrient mass retention over an even longer period and updates carbon fluxes in the wetlands. These data are crucial for accurate representation of wetland ecosystem services, particularly for those referred to by the Millennium Ecosystem Assessment (2005) as regulating services such as water purification and climate regulation.…”
Section: Introductionmentioning
confidence: 99%
“…My research has centered on wetland ecosystem ecology, system ecology, and ecological engineering. I studied long-term biogeochemical processes of water quality functions in a human-created wetland complex at the Olentangy River Wetland Research Park, the 24 th RAMSAR site in the United States (Mitsch et al, 2012). I also worked on planning, designing, and analyzing different scenarios-based restoration options for the Illinois large river-floodplain ecosystem, working with The Nature Conservancy, National…”
Section: Ecoscience + Art Initiativementioning
confidence: 99%
“…If industrial harvesting ceases at this point, it is likely to turn into wetlands with low ecological potential (Higgins and Colleran, 2006), and while it may eventually return to a 'natural' state, this would be in a timeframe outside current policy interest. Ultimately as human endeavour ceases, a new landscape rapidly emerges either by design (Mitsch et al, 2012) or by accident (Poulin et al, 2005), and thus there is a potential for regaining some of the lost ecosystem services (Wilson et al, 2012).…”
Section: Industrial Peatlands and Cultural Ecosystem Servicesmentioning
confidence: 99%